(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article describes a method for calculating the power of a gravitational micro hydroelectric power station with an air funnel. The design model of the installation operating due to the high-speed water pressure is considered. The filling factor of the turbine chamber is introduced. The dependence of the turbine output power is obtained taking into account this coefficient.